THE MAINTENANCE INTERVAL OF PREBREAKER CRITICAL COMPONENTS USING RELIABILITY-CENTERED MAINTENANCE IN PT XYZ - Haming, Puadi; Arminas, Arminas; Fajri, Nofias; Efendi, Dodi (Center for Study and Journal Management FTI UMI, 2023)
PT XYZ is a crumb rubber company that produces SIR 10 and rubber smoke sheets (RSS). As the biggest crumb rubber-produced company in Indonesia PT XYZ makes the production process sustainable. The often problem in this company is machine breakdown that occurs downtime value to be high. The highest downtime value from October 2020 until March 2021 was the Prebreaker Machine whose total downtime value was 1875 minutes. The Reliability Centered Maintenance (RCM) method is used for decreasing downtime value. The RCM is integrated with Failure Mode Effect Analysis (FMEA) for analyzing The Highest Risk Priority Number (RPN). The research results that the optimal maintenance time of the Prebreaker Machine is 51 hours which means the Prebreaker Machine is maintained after operation for 51 hours.